2008
DOI: 10.1002/ajpa.20888
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: Latent toxoplasmosis and salivary testosterone concentration—Important confounding factors in second to fourth digit ratio studies

Abstract: A sexually dimorphic characteristic, the second to fourth digit ratio (2D:4D ratio), has been shown to reflect the prenatal concentration of sex steroid hormones and to correlate with many personality, physiological, and life history traits. The correlations are usually stronger for the right than the left hand. Most studies have shown that the 2D:4D ratio does not vary with age or postnatal concentration of sex steroid hormones. Recently, a strong association between left hand 2D:4D ratio and infection with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 44 publications
(50 reference statements)
1
45
0
Order By: Relevance
“…Such a decrease was observed in infected male and female mice and in female students (Flegr, Lindová, Pivoňková, & Havlíček, 2008;Kaň-ková et al, 2011). Homosexuality, that is, the sexual attractiveness of same sex but not opposite sex subjects-the second most important dimension obtained by the factor analysis-showed no association with toxoplasmosis.…”
Section: 36mentioning
confidence: 87%
“…Such a decrease was observed in infected male and female mice and in female students (Flegr, Lindová, Pivoňková, & Havlíček, 2008;Kaň-ková et al, 2011). Homosexuality, that is, the sexual attractiveness of same sex but not opposite sex subjects-the second most important dimension obtained by the factor analysis-showed no association with toxoplasmosis.…”
Section: 36mentioning
confidence: 87%
“…Thus, genetic effects appear to have less influence on L2D:4D, which might suggest that environmental factors may be exerting stronger influences on the left hand. For example, it has been shown that human males and females infected with Toxoplasma gondii (a protozoan parasite) have low L2D:4D compared with the R2D:4D (Flegr et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…infected men are higher, have a lower second to fourth digit length ratio in the left hand (Flegr et al 2005b(Flegr et al , 2008a, i.e. have longer fingers (Kratochvíl and Flegr 2009), and their faces in photographs are rated by female raters as more dominant (Hodková et al 2007b).…”
Section: Jaroslav Flegrmentioning
confidence: 99%